Influence of Fe/Ba Molar Ratio on Phase Composition, Synthesis Temperature, Microstructure and Magnetic Properties of Barium Hexaferrite - S. S. Seyyed Afghahi; M. Jafarian (Journal of Advanced Materials in Engineering, 2017)
In this study, the effect of Fe/Ba molar ratio was investigated on the phase composition, synthesis temperature, microstructure and magnetic properties of barium hexaferrite prepared via mechanical activation. In order to synthesize this compound, Fe/Ba molar ratios of 12 and 6 were used. The effect of Fe/Ba molar ratio, milling time and heat treatment temperature for achieving the optimal conditions in producing this compound was studied. In order to study the phase, morphology and magnetic properties of the final product, X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and Vibrating Sample Magnetometer (VSM) were used respectively. According to the results, Fe/Ba molar ratio of 6, 10 h milling time and temperature of 800 °C were found to be the optimal conditions for producing this compound in a single phase. Scanning electron microscopy images show the hexagonal morphology and almost spherical particles respectively for samples prepared with Fe/Ba molar ratio equal to 12 and 6. Moreover, according to the magnetic studies, the maximum amount of saturation magnetization (56.48 emu/g) and the coercivity force (5247.2 Oe) were obtained for the sample synthesized with Fe/Ba molar ratio of 6.